2015
DOI: 10.1101/lm.039891.115
|View full text |Cite
|
Sign up to set email alerts
|

The cannabinoid system in the retrosplenial cortex modulates fear memory consolidation, reconsolidation, and extinction

Abstract: Despite the fact that the cannabinoid receptor type 1 (CB1R) plays a pivotal role in emotional memory processing in different regions of the brain, its function in the retrosplenial cortex (RSC) remains unknown. Here, using contextual fear conditioning in rats, we showed that a post-training intra-RSC infusion of the CB1R antagonist AM251 impaired, and the agonist CP55940 improved, long-term memory consolidation. Additionally, a post-reactivation infusion of AM251 enhanced memory reconsolidation, while CP55940… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 55 publications
3
9
2
1
Order By: Relevance
“…An activation of CB1 receptors with the cannabinoid agonist in the BLA induced a dose‐dependent enhancement of inhibitory avoidance memory; however, co‐infusion of the β‐adrenoceptor antagonist propranolol prevented this memory enhancement. Such an enhancement of memory consolidation by cannabinoid activation is consistent with the findings of other studies and also occurs in other brain regions . These findings thus indicate that noradrenergic signalling is required for endocannabinoids to induce memory consolidation enhancement.…”
Section: Endocannabinoid Mediation Of the Effects Of Gcs On Memorysupporting
confidence: 91%
“…An activation of CB1 receptors with the cannabinoid agonist in the BLA induced a dose‐dependent enhancement of inhibitory avoidance memory; however, co‐infusion of the β‐adrenoceptor antagonist propranolol prevented this memory enhancement. Such an enhancement of memory consolidation by cannabinoid activation is consistent with the findings of other studies and also occurs in other brain regions . These findings thus indicate that noradrenergic signalling is required for endocannabinoids to induce memory consolidation enhancement.…”
Section: Endocannabinoid Mediation Of the Effects Of Gcs On Memorysupporting
confidence: 91%
“…a). All things considered, it seems reconsolidation is the mechanism underlying remote memory rescue, which is also consistent with the effectiveness of the short reexposure time of 4 min (Bustos et al, ; de Oliveira Alvares et al, ; Sachser et al, ). Finally, we gave a further step and have shown the involvement of RE as a necessary relay between cortical and subcortical areas operating during reconsolidation (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…b), subjects were reexposed to the context 2 days after training without the US (footshocks) during 240 s, allowing both (a) to measure recent (48 h) long‐term memory recall and (b) to induce memory reactivation, whose effect was later accessed in a remote test session (38 days later). In our lab, reexposure to the context without the US for 3–5 min used to be enough to induce memory reactivation/reconsolidation (de Oliveira et al, , 2013; Sierra et al, ; Sachser et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…While time to single exposure in the training context seem to be critical to induce reconsolidation or extinction 65 , repetitive contextual exposition promotes fear extinction 66 . We have previously shown that 3-to-5 min exposure to the context induces memory reactivation/reconsolidation 2 , 36 , 37 , 67 . Accordingly, this allows us to hypothesize that caffeine administration using single memory reactivation may attenuate fear memories via reconsolidation-driven mechanism.…”
Section: Discussionmentioning
confidence: 99%